Febrile Core Temperature Is Essential for Optimal Host Defense in Bacterial Peritonitis - Jiang, Qinqqi (American Society for Microbiology, 2000)
Fever, a nonspecific acute-phase response, has been associated with improved survival and shortened disease duration in infections, but the mechanisms of these beneficial responses are poorly understood. We previously reported that increasing core temperature of bacterial endotoxin (LPS)-challenged mice to the normal febrile range modified expression of tumor necrosis factor alpha (TNF-α), interleukin 1β (IL-1β), and IL-6, three cytokines critical to mounting an initial defense against microbial pathogens, but survival was not improved in the warmer animals. We speculated that our inability to show a survival benefit of optimized cytokine expression in the warmer animals reflected our use of LPS, a nonreplicating agonist, rather than an infection with viable pathogens. The objective of this study was to determine if increasing murine core temperature altered cytokine expression and improved survival in an experimental bacterial peritonitis model. We showed that housing mice at 35.5°C rather than 23°C increased core temperature from 36.5 to 37.5°C to 39.2 to 39.7°C, suppressed plasma TNF-α expression for the initial 48 h, delayed gamma interferon expression, improved survival, and reduced the bacterial load in mice infected with Klebsiella pneumoniae peritonitis. We showed that the reduced bacterial load was not caused by a direct effect on bacterial proliferation and probably reflected enhanced host defense. These data suggest that the increase in core temperature that occurs during bacterial infections is essential for optimal antimicrobial host defense.